Muhadatsah Textbooks Based on Contextual Teaching and Learning in Islamic Boarding School l Kitab Ta’lim al-Muhadatsah ‘ala Asasi Madkhal al-Ta’lim wa al-Ta’allum al-Siyaqi fi al-Ma’had al-Islami - Prawoto, Agung; Erlina, Erlina; Koderi, Koderi; Noor, Azhar (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
This article was motivated by the problem of muhadatsah learning that there was no compatibility between the material and the student's environment. It made the students felt difficult to practice the material learned. Muhadatsah is the material to practice student conversation in Arabic. The purpose of this study was to develop a muhadatsah textbook based on contextual teaching and learning. The data of this study were obtained from interviews with muhadatsah teachers, field observations and questionnaires to experts. This book was suitable for teaching conversation and in accordance with the results of product evaluations from experts and product experiment results from students. The results of the product evaluation from the material expert were 93%, from Arabic Language expert were 94% and from design expert were 91%. The product trial results from the students were 88%. The development of muhadatsah textbooks based on contextual teaching and learning had a significant effect on improve speaking skills, improving student learning outcomes and making students more active in learning. Hence, this paper suggested the teacher and institution in solving the problems in Arabic learning especially muhadatsah.